Sobre la presencia de Dictyota mediterranea (Schiffner) G. Furnari (Dictyotales, Phaeophyceae) en la Península Ibérica. - Pena Martín, Carolina; Gómez Garreta, Amelia; Crespo, Manuel B. (Acta Botanica Malacitana, 2004)
On the presence of Dictyota mediterranea (Schiffner) G. Furnari (Dictyotales, Phaeophyceae) in the Iberian Peninsula. Palabras clave. Dictyota mediterranea, Dictyotales, Phaeophyceae, algas marinas, corología, anatomía. Key words. Dictyota mediterranea, Dictyotales, Phaeophyceae, marine algae, chorology, anatomy.